Anti-aggregation effect of carbon quantum dots on diabetogenic and beta-cell cytotoxic amylin and beta amyloid heterocomplexes. Issue 39 (27th September 2022) - Voronova, Anna; Barras, Alexandre; Plaisance, Valérie; Pawlowski, Valerie; Boukherroub, Rabah; Abderrahmani, Amar; Szunerits, Sabine
Abstract : The diabetogenic environment of β-cell islets directly participates in the formation of amyloid aggregates in type 2 diabetics, an effect that can be reversed using carbon quantum dots. Abstract : Pancreatic islet amyloid deposition is a pathological hallmark of Type 2 diabetes (T2D), contributing to reduced functional β-cell mass. Islet amyloids result not only from the aggregation and fibrillation of human islet amyloid polypeptide (hIAPP), but also from beta-amyloid 42 (Aβ42), the key amyloidogenic peptide linked to Alzheimer's disease. Importantly, Aβ42 and hIAPP aggregates (IAPP:Aβ42) can interact with each other and form some harmful heterocomplex fibrils. While it is well-documented that hIAPP aggregation occurs only when islets are exposed to a diabetic environment, including hyperglycemia and/or elevated concentrations of saturated fatty acids (SFAs), it remains unclear if hIAPP and IAPP:Aβ42 heteromer fibrillations are directly or indirectly triggered by this environment. In this study, we show the interplay between high glucose concentrations and palmitate as the SFA in the aggregation of hIAPP. In addition, we outline that the interaction of hIAPP and Aβ42 leads to the formation of complex protein aggregates, which are toxic to β-cells. Carbon nanocolloids in the form of positively charged carbon quantum dots (CQD-pos) efficiently prevent single amyloid aggregation and the formation of IAPP:Aβ42 heterocomplexes. We provide clear evidence with this study that the diabetogenic environment of islets could directly contribute to the formation of homomeric and heteromeric amyloid aggregates and fibrils in T2D. We also propose carbon nanocolloids as biocompatible nanomaterials for developing innovative therapeutic strategies that prevent the decline of functional β-cell mass.